PENGARUH PERAN KEPEMIMPINAN DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KOTA PEMATANGSIANTAR - Simanjuntak, Lamtiur; Lie, Darwin; Efendi, Efendi; Inrawan, Ady (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
As for the purpose of this research is: 1. To know the description of leadership role and teamwork of the employees performance at BKD Kota Pematangsiantar. 2. To know the influence of leadership and teamwork of employees performance at BKD Kota Pematangsiantar. This research was done with field research design and library research. As for the population used by the author in this research is as much as 43 correspondents, that is employees at BKD Kota Pematangsiantar. The data collection was done with questionnaire, interview, documentation and observation. The analysis technique used in this research was multiple liniar regression, correlation coefficient and determination as well as the test of hyphothesis with t test and F test.        The results of the study can be summarized as follows: 1. Employees stated that leadership in this company is high, teamwork and employees performance in this company is good. 2. The analysis regression is Ŷ = 24,495 + 0,395 X1 + 0,991 X2,means that leadership and teamwork has good effect to employees performance.3. Analysis correlation obtained r value = 0,793, means that there is moderately high and positive correlation between leadership and teamwork with employees performance. High low employees performance can be explained by leadership and teamwork amounting to 62,8% while the rest is 37,2,0% affected by other factor like motivation, competence, compensation, carrier development and management support. 4. The research hyphothesis of H0is rejected, means that leadership and teamwork simultaneously have positive affect and significant to employees performance at BKD Kota Pematangsiantar.                     The suggestion from this research is to the improve of have care about the work of employees performance leadership The need to strengthen kinship ties with employees through first familiar to every employee. To improve teamwork then the leadership needs to make good communication by the leadership to employees, such as giving an opportunity to the employee to convey his statement..Keywords: Leadership Role, Teamwork and Employees Performance.